2012
DOI: 10.1371/journal.pone.0038985
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Roles of Clock Genes in Retinal and Suprachiasmatic Nucleus Circadian Oscillators

Abstract: The retina is both a sensory organ and a self-sustained circadian clock. Gene targeting studies have revealed that mammalian circadian clocks generate molecular circadian rhythms through coupled transcription/translation feedback loops which involve 6 core clock genes, namely Period (Per) 1 and 2, Cryptochrome (Cry) 1 and 2, Clock, and Bmal1 and that the roles of individual clock genes in rhythms generation are tissue-specific. However, the mechanisms of molecular circadian rhythms in the mammalian retina are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 36 publications
7
49
0
1
Order By: Relevance
“…Our results indicate that at the level of the retina, this is an oversimplification. This is consistent with emerging data where CRY1 and -2 appear to serve distinct and separate functions (24, 42, 43), including differences in the timing of their genomic interactions (44). It has previously been suggested that the mechanism underlying circadian rhythm generation in the retina differs from that in the SCN.…”
Section: Discussionsupporting
confidence: 91%
“…Our results indicate that at the level of the retina, this is an oversimplification. This is consistent with emerging data where CRY1 and -2 appear to serve distinct and separate functions (24, 42, 43), including differences in the timing of their genomic interactions (44). It has previously been suggested that the mechanism underlying circadian rhythm generation in the retina differs from that in the SCN.…”
Section: Discussionsupporting
confidence: 91%
“…A few other brain regions have also been shown to have the independent capacity to generate circadian rhythms independently of the SCN pacemaker [90]. The best-studied of these regions are the olfactory bulbs [91] and retina [92], but the Hb, and particularly the LHb, has also been shown to generate circadian firing-rate rhythms for at least a few cycles in vitro, and to generate circadian rhythms of clock gene expression [93,94]. The LHb is further linked to the circadian system because it receives a vasopressin-containing projection from the SCN, which plays an important role in conveying circadian information [95,96], and cells in the LHb respond to light input similarly to SCN neurons [93].…”
Section: Sleep and Circadian Rhythmsmentioning
confidence: 99%
“…Only one study has extensively explored the rhythmic phenotype of single clock gene knockout in retina. Using several clock-gene-deficient mice, Ruan et al 21 reported that the retinal clock is more vulnerable to clock gene disruption than the SCN. The authors showed that Per1, Cry1, and Clock are each necessary for the expression of molecular circadian rhythms by the retina.…”
Section: Cry1mentioning
confidence: 99%
“…By contrast, knocking out Per2, Per3, or Cry2 individually does not blunt the rhythm but modulates its period or amplitude. 21 For example, retinal explants from…”
Section: Cry1mentioning
confidence: 99%